Interaction analyses of 14-3-3ζ, Dok1, and phosphorylated integrin β cytoplasmic tails reveal a bi-molecular switch in integrin regulation - Chatterjee, Deepak (2020)
Integrins are hetero-dimeric (α and β subunits) type I transmembrane proteins that facilitate cell adhesion and migration. The cytoplasmic tails (CTs) of integrins interact with a plethora of intra-cellular proteins that are required for integrin bidirectional signaling. In particular, the β CTs of integrins are known to recruit a variety of cytosolic proteins that often have overlapping recognition sites. However, the chronological sequence of β CTs/cytosolic proteins interactions remains to be fully characterized. Previous studies have shown that the scaffold protein 14-3-3ζ binds to phosphorylated β CTs in activated integrins, whereas interactions of Dok-1 with phosphorylated β CTs maintained integrins in the resting state. In this study, we examined the binding interactions between 14-3-3ζ, Dok1, and phosphorylated integrin β2 and β3 CTs. We show that the scaffold protein 14-3-3ζ interacts with the phosphotyrosine binding (PTB) domain of Dok1 even in the absence of the phosphorylated integrin β CTs. The interactions were mapped onto the β-sheet region of the PTB domain of Dok1. Furthermore, we provide evidence that the 14-3-3ζ/Dok1 binary complex is able to bind to their cognate phosphorylated sequence motifs in the integrin β CTs. We demonstrate that Thr phosphorylated pTTT β2 CT or pTST β3 CT can bind to 14-3-3ζ that is in complex with the Dok1 PTB domain, whereas Ser phosphorylated β2 CT or Tyr phosphorylated β3 CT interacted with Dok1 in 14-3-3ζ/Dok1 complex. Based on these data, we propose that 14-3-3ζ/Dok1 complex could serve as a molecular switch providing novel molecular insights into the regulating integrin activation.